Association between the risk of lung cancer and influenza: A population-based nested case-control study. (November 2019) - Weng, Ching-Fu; Chen, Li-Ju; Lin, Chih-Wan; Chen, Ho-Min; Lee, Henry Hsin-Chung; Ling, Thai-Yen; Hsiao, Fei-Yuan
Highlights: Previous studies have shown influenza virus can lead to tumorigenesis; however, no clinical studies have been conducted to test this hypothesis. We found exposure to influenza was associated with an increased risk of lung cancer and the risk increased with cumulative exposure to influenza. We hope to encourage more investigations to better understand the mechanisms and explore potential solutions to prevent and treat lung cancer. Abstract: Background: Previous animal studies have shown that certain respiratory oncoviruses can lead to tumorigenesis, especially influenza virus. However, no clinical studies other than animal studies have been conducted to test this hypothesis. Objective: To investigate the association between influenza and the risk of lung cancer using the Taiwan Cancer Registry Database (TCRD) and Taiwan's National Health Insurance Research Database (NHIRD). Methods: We identified a study cohort consisting of patients aged 40 years or above who were enrolled in the NHIRD between 1 January 2012 and 31 December 2014. Among them, we identified patients with lung cancer (cases) and their matched controls (matched by age, sex, and disease risk score (DRS) at a ratio of 1:10). Multivariate conditional logistic regression models were used to evaluate the association between exposure to influenza (timing and cumulative number) and risk of lung cancer. Results: We identified 32, 063 cases and 320, 627 matched controls. Influenza was associated with a 1.09-fold increased risk of lung cancer (aOR 1.09, 95% CI 1.04–1.14, p < 0.0001). The risk of lung cancer increased slightly with cumulative exposure to influenza (1–2 exposures: aOR 1.05, 95% CI 1.00–1.11; 3-4 exposures: aOR 1.12, 95% CI 1.00–1.25; 5+ exposures: aOR 1.25, 95% CI 1.13–1.39). Conclusion: Exposure to influenza was associated with an increased risk of lung cancer and the risk increased with cumulative exposure to influenza. However, the lack of valid information on smoking could lead to confounding, and future studies collecting patients' smoking histories are warranted to validate the association between influenza and lung cancer.